2008
DOI: 10.1158/0008-5472.can-07-5953
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 4 Induces p27Kip1 Expression in and Suppresses the Growth and Metastasis of Human Pancreatic Cancer Cells

Abstract: The zinc finger transcription factor Krüppel-like factor 4 (KLF4) has been implicated in both tumor suppression and progression. However, its function in pancreatic cancer has not been well characterized. Here, we show that pancreatic cancer cell lines expressed various levels of KLF4 RNA and protein. Ectopic expression of KLF4 by FG and BxPC-3 pancreatic cancer cells resulted in cell cycle arrest and marked inhibition of cell growth in vitro and attenuation of tumor growth and metastasis in an orthotopic mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
130
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 46 publications
11
130
3
2
Order By: Relevance
“…Recently, KLF4 has been shown to inhibit cell migration and invasion in TE2 of human ESCC cell line (28). In addition, KLF4 can inhibit pancreatic cancer metastasis in vivo (23). Consistent with these results, KLF4 overexpression reduces cell migration and invasion in RKO colon cancer cells (29).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Recently, KLF4 has been shown to inhibit cell migration and invasion in TE2 of human ESCC cell line (28). In addition, KLF4 can inhibit pancreatic cancer metastasis in vivo (23). Consistent with these results, KLF4 overexpression reduces cell migration and invasion in RKO colon cancer cells (29).…”
Section: Discussionsupporting
confidence: 59%
“…In line with these studies, the loss of KLF4 expression has been reported in several human tumors, including colorectal, stomach, esophageal, and bladder cancers (22)(23)(24)(25), which indicates its tumor suppressor role. However, KLF4 also exhibits oncogenic properties.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30] The lack of KLF4 expression has previously been reported in other types of tumors, especially in large bowel and gastric adenocarcinomas, [31][32][33] and it has also been associated with an aggressive evolution in gastric cancer. 33 Likewise, suppression of growth and metastasis in human pancreatic cancer cells by KLF4 expression has been described, 34 suggesting that it may behave as a suppressor gene. Conversely, and in contrast to the consideration of KLF4 as a tumor suppressor protein, 3 laboratories have identified it as a potential oncogene.…”
Section: 23mentioning
confidence: 99%
“…Negative regulation of KLF4 by Notch signalling has been observed in intestinal epithelium or colorectal cancer cells 37,38 and these results are in favour of the tumour suppressor role of KLF4 in colorectal cancer cells 39 . In contrast to the tumour suppressor role of KLF4 in colorectal cancer cells/intestinal epithelium and pancreatic cancer [37][38][39][40][41] , other groups have demonstrated the oncogenic role of KLF4 in breast cancer and HNC [42][43][44] . These findings are consistent with our discovery that KLF4 plays an oncogenic role, especially in HNSCC 44 .…”
Section: Oecm1-twist1mentioning
confidence: 98%